2019
DOI: 10.1002/jso.25488
|View full text |Cite
|
Sign up to set email alerts
|

Early versus standard closure of temporary ileostomy in patients with rectal cancer: A randomized controlled trial

Abstract: Background and Objectives A significant proportion of patients undergoing rectal cancer surgery receive a temporary ileostomy because of its benefits in case of anastomotic dehiscence. However, the best timing for closure remains unclear. Methods Early closure (EC; 30 days after creation) and standard closure (SC; 90 days after creation) of ileostomy were compared in a single‐center randomized controlled trial conducted at National Cancer Institute (Vilnius, Lithuania). Patients with a temporary ileostomy who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 25 publications
0
54
0
2
Order By: Relevance
“…19,20 A temporary ileostomy may not prevent the AL but rather diminish its symptoms and consequences. Further, the true rate of AL in patients receiving ileostomy may be underestimated because usually asymptomatic patients do not undergo testing for anastomosis integrity at the early postoperative period 21,22 Similar, in our study, asymptomatic patients underwent anastomosis integrity testing just before the ileostomy closure, thus some cases of AL in patients who receive ileostomy might have been underestimated as well. Therefore, further studies are required to clarify the role of ileostomy in the prevention of the AL.…”
Section: Discussionmentioning
confidence: 57%
“…19,20 A temporary ileostomy may not prevent the AL but rather diminish its symptoms and consequences. Further, the true rate of AL in patients receiving ileostomy may be underestimated because usually asymptomatic patients do not undergo testing for anastomosis integrity at the early postoperative period 21,22 Similar, in our study, asymptomatic patients underwent anastomosis integrity testing just before the ileostomy closure, thus some cases of AL in patients who receive ileostomy might have been underestimated as well. Therefore, further studies are required to clarify the role of ileostomy in the prevention of the AL.…”
Section: Discussionmentioning
confidence: 57%
“…On the opposite, the early closure of ileostomy after radical rectal resection was found not safe in a RCT comparing early closure (30 days after creation) and standard closure (90 days after creation). The overall 30 days postoperative morbidity rate was dramatically higher in the EIR group (27.9% vs 7.9%; P = 0.024) the authors concluded that EIR should not be performed (5).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the best timing for ileostomy reversal, early or late after its formation and the proper technique used for its closure are still unclear and controversial (4)(5)(6)(7)(8)(9)(10). Regardless the surgical technique, a significant morbidity can be associated with the reversal procedure (8,11).…”
Section: Introductionmentioning
confidence: 99%
“…The next clinical question to be answered is, what is the best timing for stoma closure within 90 days? A clinical trial demonstrated that stoma closure at 30 days after the initial operation increased the rate of severe postoperative complications when compared with that of late stoma closure [18]. Although the authors could not explain the reasons for their results, adhesion at 30 days after the initial operation could be worse than after a longer period, and di culties during the operation might result in higher occurrence of severe postoperative complications.…”
Section: Discussionmentioning
confidence: 97%